2016
DOI: 10.3390/s16071066
|View full text |Cite
|
Sign up to set email alerts
|

Stair-Walking Performance in Adolescents with Intellectual Disabilities

Abstract: Most individuals with intellectual disabilities (ID) demonstrate problems in learning and movement coordination. Consequently, they usually have difficulties in activities such as standing, walking, and stair climbing. To monitor the physical impairments of these children, regular gross motor evaluation is crucial. Straight-line level walking is the most frequently used test of their mobility. However, numerous studies have found that unless the children have multiple disabilities, no significant differences c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…This result does not seem to fit the real situation considering that walking upstairs should be more stable than walking downstairs. Walking downstairs is riskier than walking upstairs because of the acceleration added by gravity [ 24 ]. A past study by Chang Gung Medical Foundation also found that 10% of falling cases in the elderly in Taiwan were caused by walking upstairs and walking downstairs with more cases in walking downstairs [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…This result does not seem to fit the real situation considering that walking upstairs should be more stable than walking downstairs. Walking downstairs is riskier than walking upstairs because of the acceleration added by gravity [ 24 ]. A past study by Chang Gung Medical Foundation also found that 10% of falling cases in the elderly in Taiwan were caused by walking upstairs and walking downstairs with more cases in walking downstairs [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…It can be assumed that with the lack of integration between the various mechanisms responsible for maintaining the body balance, people with ID compensate their dysfunction by lowering the COG. When adolescents with ID had been analysed during stair climbing, the lowering of the COG as a manner to increase the perception of a safety zone was indicated (Shieh et al 2016). This can result in fixation of the flexion in the hip joints and in destabilisation of muscle tone within the lower leg and ankle joints, which reduces the functional stabilisation of the lower limbs and can contribute to increased sway in the AP direction.…”
Section: Discussionmentioning
confidence: 99%
“…The first limitation is the relatively small number of participants involved in the programs and the consequent difficulty to determine the strength of the present findings and to shed some light on the performance differences across participants. New studies would need to extend the assessment, which should also include follow-up data ( 31 , 40 ). The second limitation concerns the lack of any specific data regarding (a) the possible benefits of the participants’ response performance (exercise) and (b) the supposed enjoyment of such performance ( 15 ).…”
Section: Discussionmentioning
confidence: 99%